2011
DOI: 10.1186/1471-2261-11-67
|View full text |Cite
|
Sign up to set email alerts
|

Association between carotid area calcifications and periodontal risk: a cross sectional study of panoramic radiographic findings

Abstract: BackgroundThe aim was to investigate the extent to which it is possible to diagnose suspected carotid calcification from dental panoramic radiography (PR) and to establish an association to periodontal risk.Methods824 PRs from one dental practice were investigated. Parameters considered were gender, age, bone loss - age index, tooth loss, periodontal risk and suspected carotid calcification (left, right, both sides). Periodontal risk was classified: low risk (under 4 missing teeth, bone loss - age index under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 55 publications
4
11
0
1
Order By: Relevance
“…For example, Bengtsson et al () found a significant association between periodontitis and CAC as measured from PANs in the aging population. However, Tiller et al () found no such association when multivariate regression analysis was performed. Ohba et al () also did not show any differences in periodontal disease severity or number of teeth between subjects with or without CAC.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Bengtsson et al () found a significant association between periodontitis and CAC as measured from PANs in the aging population. However, Tiller et al () found no such association when multivariate regression analysis was performed. Ohba et al () also did not show any differences in periodontal disease severity or number of teeth between subjects with or without CAC.…”
Section: Discussionmentioning
confidence: 97%
“…Potential factors influencing periodontitis include age, sex, smoking, education, personal habits, and socioeconomic and health status (Genco and Borgnakke, ). Although many researchers controlled confounding factors influencing periodontitis or CVD (Persson et al , ; Desvarieux et al , ; Tiller et al , ), some investigators did not use multivariate analysis to adjust for these risk factors, making it difficult to clearly determine the relationship (Ravon et al , ; Beckstrom et al , ; Bengtsson et al , ). Our study collected comprehensive data on traditional cardiovascular and periodontal risk factors and was strengthened by analyzing these as covariates in statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Taguchi 17 ve arkadaşları 2013 yılın-da yaptıkları bir çalışmada karotis arter kalsifikasyonu olan hastaların %2,45'inde osteoporoz belirlemişlerdir. Tiller 18 ve arkadaşları da 2011 yılında yaptıkları bir çalışmada periodontal riski yüksek olan hastalarda karotid bölge kalsifikasyonlarına daha fazla rastlandığını bulmuşlar ve bu durumu diyabetes mellitus ve sigara kullanımıyla ilişkilendirmişlerdir.…”
Section: Arteriyelunclassified
“…In contrast, Tiller et al [56] failed to show a significant periodontitis risk and radiographic evidence of carotid calcification on PMX when multivariate regression analysis was performed. It should also be recognized that the study by Tiller et al [56] studied the risk of periodontitis and not a diagnosis of periodontitis.…”
Section: Carotid Calcification and Periodontitismentioning
confidence: 89%
“…In individuals with periodontitis, defined as > 1 mm bone loss on a panoramic radiograph, 25.7% of individuals with bilateral carotid calcifications had periodontitis compared to 10.4% among those without carotid calcifications [26]. In contrast, Tiller et al [56] failed to show a significant periodontitis risk and radiographic evidence of carotid calcification on PMX when multivariate regression analysis was performed. It should also be recognized that the study by Tiller et al [56] studied the risk of periodontitis and not a diagnosis of periodontitis.…”
Section: Carotid Calcification and Periodontitismentioning
confidence: 99%